Highest Achievable Outcomes for Patients Undergoing Cervical Deformity Corrective Surgery by Frailty. Issue 5 (9th November 2022) - Passias, Peter G.; Kummer, Nicholas; Williamson, Tyler K.; Moattari, Kevin; Lafage, Virginie; Lafage, Renaud; Kim, Han Jo; Daniels, Alan H.; Gum, Jeffrey L.; Diebo, Bassel G.; Protopsaltis, Themistocles S.; Mundis, Gregory M.; et al.
Abstract : BACKGROUND: Frailty is influential in determining operative outcomes, including complications, in patients with cervical deformity (CD). OBJECTIVE: To assess whether frailty status limits the highest achievable outcomes of patients with CD. METHODS: Adult patients with CD with 2-year (2Y) data included. Frailty stratification: not frail (NF) <0.2, frail (F) 0.2 to 0.4, and severely frail (SF) >0.4. Analysis of covariance established estimated marginal means based on age, invasiveness, and baseline deformity, for improvement, deterioration, or maintenance in Neck Disability Index (NDI), Modified Japanese Orthopaedic Association (mJOA), and Numerical Rating Scale Neck Pain. RESULTS: One hundred twenty-six patients with CD included 29 NF, 83 F, and 14 SF. The NF group had the highest rates of deterioration and lowest rates of improvement in cervical Sagittal Vertical Axis and horizontal gaze modifiers. Two-year improvements in NDI by frailty: NF: −11.2, F: −16.9, and SF: −14.6 ( P = .524). The top quartile of NF patients also had the lowest 1-year (1Y) NDI (7.0) compared with F (11.0) and SF (40.5). Between 1Y and 2Y, 7.9% of patients deteriorated in NDI, 71.1% maintained, and 21.1% improved. Between 1Y and 2Y, SF had the highest rate of improvement (42%), while NF had the highest rate of deterioration (18.5%). CONCLUSION: Although frail patients improved more often by 1Y, SF patients achieve most of their clinical improvement between 1 and 2Y. Frailty is associated with factors such as osteoporosis, poor alignment, neurological status, sarcopenia, and other medical comorbidities. Similarly, clinical outcomes can be affected by many factors (fusion status, number of pain generators within treated levels, integrity of soft tissues and bone, and deformity correction). Although accounting for such factors will ultimately determine whether frailty alone is an independent risk factor, these preliminary findings may suggest that frailty status affects the clinical outcomes and improvement after CD surgery. Abstract :